(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
Social Work Artfully: Beyond Borders and Boundaries emerged from a meeting between Dr. Hazel Barnes (from Johannesburg) and Christine Sinding (from Ontario), while at the 2010 African Research Conference. This fruitful initial encounter, along with subsequent conversations, set the stage for the creation of both a series of international workshops and what would become Social Work Artfully.